Better with Bologna? Tertiary education reform and student outcomes - Sabrina Hahm; Jochen Kluve (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2017)
This paper analyzes impacts of the Bologna Reform for Germany by using unique micro data from Humboldt-Universität zu Berlin. Variation in treatment introduction generates exogenous assignment of students into a treatment (Bachelor) and control group (Diploma). We account for potentially remaining selection bias by estimating a 2SLS model. Our results indicate i.a. that the reform led to a significant and sizeable increase in the probability of graduating within planned instructional time.
Keywords: 330